Effect of 2D and 3D coil on the dynamic mold temperature control by induction heating - Son Minh, Pham (Vietnam Journal of Science and Technology, 2014)
Electromagnetic induction heating has many advantages such as fast heating, low energy consumption and reduced environmental pollution. Using induction heating for rapid tool heating is more economical and efficient than any of the current tool heating techniques. In this research, using both experiment and simulation, the 2D and 3D design of induction coil were applied to verify the heating capacity of mold plate. With the 2D coil, after 2 s for heating, the temperature of mold plate can increase from 40 oC to 108 oC. However, the low temperature area appears at the center of the mold plate. On the contrary, when the 3D design was used, the max temperature reached to 89 oC at the end of heating period, and the low temperature area was removed.